Effect of tannins on the in vitro growth of Clostridium perfringens - Elizondo, Ana M. (2010)
Vegetable tannins are water-soluble polyphenolic compounds of varying molecular weights that occur abundantly in nature. The diet of many free-ranging wild animals contains significant amounts of tannins. Also, commercial tannins are used in animal industry as food additives to improve animal performance. In order to further determine the capacity of tannins to inhibit the development of intestinal diseases produced by Clostridium pefringens, we evaluated here the effect of tannins from quebracho, chestnut or combinations of both on C. perfringens and their toxins. The C. perfringens (types A, B, C, D and E) growth obtained from the intestine of healthy and diseased animals was reduced in a dose-dependent manner in the presence of quebracho tannins, chestnut tannins, combinations of both or a commercial formula based in these tannins. Although the minimal inhibitory concentration of both tannins varied between isolates, no statistically significant differences were observed between isolates from healthy or sick animals. Comparative analysis showed that the concentrations of quebracho tannin inhibiting the growth of C. perfringens were higher than chestnut tannin. In fact, antibacterial effect of quebracho tannin was increased up to 20 times with the addition of 25% of chestnut tannin and 85 times with 75% of chestnut tannin. Antibacterial activity of the commercial product was up to ~50 times higher than quebracho tannin alone. Quebracho tannin showed partial bactericidal activity, whereas chestnut tannin activity was stronger. Both tannins were able to reduce the alpha toxin lecithinase activity and epsilon toxin cytotoxicity in MDCK cells. These results suggest that tannin-supplemented diet could be useful to prevent some clostridial diseases.